Subcutaneous apomorphine in advanced Parkinson's disease and its use in Indian population - Metta, Vinod; Borgohain, Rupam; L Kukkle, Prashanth; Mridula, Rukmini; Agarwal, Pankaj; Kishore, Asha; Goyal, Vinay; Chaudhuri, Ray (Annals of Movement Disorders, 2020)
Although subcutaneously administered apomorphine is widely used as an effective adjunct therapy for Parkinson's disease (PD), it was approved for use in India only in 2019. This review summarizes the history, pharmacology, clinical spectrum, indications, efficacy, and side effects of subcutaneous apomorphine use in patients with PD along with clinical recommendations for its use in Indian context. Intermittent subcutaneous apomorphine injection or continuous subcutaneous apomorphine infusion is effective adjunctive treatments for patients with advanced PD with levodopa-related refractory motor complications and some specific nonmotor symptoms (NMS) as growing evidence shows apomorphine also improves aspects of NMS of PD. Common side effects of subcutaneous apomorphine are skin nodules, nausea, and somnolence with incidence being higher with infusion than that with injection. Impulse control disorders and neuropsychiatric complications common to most dopamine agonists can also occur. As per National Institute for Health and Care Excellence (NICE), United Kingdom, apomorphine, as intermittent injection or continuous subcutaneous infusion, is one of the best medical therapies and may be considered before using deep brain stimulation (DBS) or levodopa/carbidopa intestinal gel (LCIG). Head-to-head open-label comparative multicenter data suggest that apomorphine is at least as effective as DBS or LCIG in relation to nonmotor and motor benefit. More studies are needed to reduce the paucity of apomorphine data in Indian population. We also discuss criteria to select one device therapy over another and newer apomorphine delivery strategies in the pipeline.